2016
DOI: 10.4236/ns.2016.83016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Induced Changes in Human Lipid Composition as Revealed through XPS-Analysis

Abstract: In this study two plasma sources were used for an in vivo treatment of human stratum corneum. The sample preparation was realised with the Cyanoacrylat stripping method, whereby a few layers of corneocytes embedded in the lipid matrix were removed from the skin of healthy volunteers. For the plasma treatment, dielectric barrier discharges with pulse durations in the microsecond as well as in the nanosecond range were applied. A comparison of these sources with respect to their biologically active components in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Lipids exposed to plasma are degraded. Studies by Marschewski et al 10) and Hirschberg et al 11) showed that plasma exposure raised the oxygen and nitrogen atom concentration in skin lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids exposed to plasma are degraded. Studies by Marschewski et al 10) and Hirschberg et al 11) showed that plasma exposure raised the oxygen and nitrogen atom concentration in skin lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma discharge is capable of creating many reactive particles. Investigation of the interaction of the air plasma with the skin lipids was presented by Marchewski et al 12) and Hirschberg et al 13) These works showed that the plasma-treated lipids increased the concentration of oxygen and nitrogen atoms in the samples, suggesting oxidation and nitration of the lipids or lipid removal. Molecular dynamics simulation of OH and O radical reaction with α-linolenic acids (non-saturated fatty acid) demonstrated the creation of double bonds, alcohol or aldehyde formation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with another but very similar DBD and a related setup, sample heating was analyzed. This revealed that one minute of plasma treatment only marginally increased sample temperatures [160]. Hence, no thermal injury is to be expected from applications with the µs-pulsed DBD.…”
Section: Gas Temperature and Thermal Outputmentioning
confidence: 91%
“…The calculation of the effective irradiance produced by the kINPen ® MED was based on measurements with a calibrated optic spectrometer system [138]. The spectral irradiance of the µs-pulsed DBD plasma was calculated after detection of the irradiance with a calibrated radiometer [160]. The results showed that no radiation in the UVC region (200-280 nm) was generated by either of the two APP devices [47,138].…”
Section: Optical Artificial Radiation (Uv Radiation)mentioning
confidence: 99%